1999
DOI: 10.1074/jbc.274.31.21735
|View full text |Cite
|
Sign up to set email alerts
|

The Diadenosine Hexaphosphate Hydrolases fromSchizosaccharomyces pombe and Saccharomyces cerevisiae Are Homologues of the Human Diphosphoinositol Polyphosphate Phosphohydrolase

Abstract: J. Biol. Chem. 274, 8604 -8610) have both previously been characterized as MutT family hydrolases with high specificity for diadenosine hexa-and pentaphosphates (Ap 6 A and Ap 5 A). Using purified recombinant preparations of these enzymes, we have now discovered that they have an important additional function, namely, the efficient hydrolysis of diphosphorylated inositol polyphosphates. This overlapping specificity of an enzyme for two completely different classes of substrate is not only of enzymological sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
133
1

Year Published

1999
1999
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 130 publications
(137 citation statements)
references
References 46 publications
2
133
1
Order By: Relevance
“…It has been demonstrated that some proteins with the Nudix motif act on nonnucleotide substrates such as diphosphoinositol polyphosphates (Safrany et al, 1998(Safrany et al, , 1999, 5-phosphoribosyl 1-pyrophosphate (Fisher et al, 2002), and thiamine pyrophosphate (Lawhorn et al, 2004). Therefore, it seems likely that AtNUDXs with no activity toward any substrate tested here would act on nonnucleotide substrates or be inactive following expression in E. coli and/or purification by affinity chromatography.…”
Section: Atnudxs With No Activitymentioning
confidence: 93%
“…It has been demonstrated that some proteins with the Nudix motif act on nonnucleotide substrates such as diphosphoinositol polyphosphates (Safrany et al, 1998(Safrany et al, , 1999, 5-phosphoribosyl 1-pyrophosphate (Fisher et al, 2002), and thiamine pyrophosphate (Lawhorn et al, 2004). Therefore, it seems likely that AtNUDXs with no activity toward any substrate tested here would act on nonnucleotide substrates or be inactive following expression in E. coli and/or purification by affinity chromatography.…”
Section: Atnudxs With No Activitymentioning
confidence: 93%
“…PP-InsP 5 and [PP] 2 -InsP 4 are present at 100-fold lower levels than InsP 6 , as is the case in higher eukaryotes [17]. This is the ¢rst time that PP-InsP 5 and [PP] 2 -InsP 4 have been identi¢ed in any yeast, although their presence was anticipated, following earlier identi¢cation of a kinase from S. cerevisiae that synthesizes PP-InsP 5 [4] and the discovery of a diphosphoinositol polyphosphate phosphatase from the same organism [12].…”
Section: Analysis Of Ipmk Activity In Vitromentioning
confidence: 94%
“…drolase) [6] and diphosphoinositol polyphosphate phosphohydrolase (DIPP) [7]. DIPP is homologous with the recently described Ap ' A hydrolases from budding and fission yeasts and, like them, is remarkable in its ability to hydrolyse the nonnucleotide diphosphoinositol polyphosphates in addition to the structurally unrelated diadenosine polyphosphates [8]. A survey of the GenBank expressed sequence tag (EST) database suggests the existence of at least six further human MutT motif proteins, including a protein encoded in an anti-sense transcript of the basic fibroblast growth factor gene [9], a protein closely related to DIPP (DIPP2) [7], and a homologue of the Saccharomyces cere isiae YSA1 protein.…”
Section: Introductionmentioning
confidence: 99%